Racial disparities in education debt burden among low- and moderate-income households. (June 2016) - Grinstein-Weiss, Michal; Perantie, Dana C.; Taylor, Samuel H.; Guo, Shenyang; Raghavan, Ramesh
Abstract: Evidence now demonstrates significant variation in education-debt levels by race and household income, with Black and lower-income students accumulating higher levels of education debt compared to their White and upper-income peers. This study is one of the first to evaluate whether racial disparities in education debt extend to a low- and moderate-income (LMI) population. With data from a national sample of LMI households in the Refund to Savings study ( N = 17.684), we employ a two-part modeling approach with a matching-estimator robustness check to estimate racial and ethnic variation in education debt. We find that significant disparities in education debt remain: the odds of student loan indebtedness are twice as high for LMI Black students as for White counterparts. In all, LMI Black students are estimated to incur 7721 more in education debt than LMI Whites, with disparities persisting after graduation. These findings suggest that LMI Black and White students, who face similar liquidity constraints and borrowing risks, are at unequal risk of accumulating education debt. We conclude by discussing the implications of this research for asset-building policies and student loan repayment efforts, both of which offer promise in bolstering college affordability and easing the burden of education debt. Highlights: Racial disparities in education debt have been established. This study analyzed Black-White variation in education debt among a low- and moderate-income (LMI) population. Significant variation in education debt was found, as LMI Black students accrued 7, 721 more education debt than LMI Whites. Significant Black-White disparities in education debt persisted after accounting for degree completion and socioeconomic factors.